Strategy in Nonprofit Organisations: A Systematic Literature Review and Agenda for Future Research - Laurett, Rozelia (2018)
This study aims to present the progress and development in research carried out on the strategies put into practice at nonprofit organisations. To this end, we carried out a systematic review of the literature making recourse to the ISI Web of Knowledge platform for the data collection process that resulted in the 62 scientific articles (published between 1981 and 2016) analysed in this review. This analysis correspondingly sets out a description of the studies, a timeframe for their respective dates of publication and details about the research methods applied. The results convey how, over the last four decades, there have been a range of studies of nonprofit organisation strategy-related themes with the greatest incidence clustered around the terms strategic management, strategic planning, strategic typology (Miles and Snow 1978), innovation strategies and the strategic management of human resources. We found that the 1980s focused on the theoretical foundations of strategy in nonprofit organisations and the 1990s showed a theoretical consolidation of strategy in nonprofit organisations. The first decade of the twenty-first century shows a focus on improving the management of nonprofit organisations, and in the past decade there has been a diversification in the strategies adopted by these organisations. We furthermore set out suggestions for future research alongside the theoretical and practical implications of this study.